A Minimization of Fuel Costs in Pharmaceutical Distribution Using Clarke-Wright Savings Heuristic and Nearest Neighbor Methods - Mutiara Azahra; Muhammad Habiburrohman (MATHunesa: Jurnal Ilmiah Matematika, 2025)
Distribution plays a vital role in the pharmaceutical industry as it directly affects operational efficiency and the timeliness of product delivery to healthcare facilities. Distribution efficiency, particularly in terms of fuel consumption, poses a significant challenge for pharmaceutical companies especially amid fluctuating fuel prices and the complexity of distribution networks. This study aims to optimize pharmaceutical distribution routes using two heuristic methods: Clarke-Wright Savings Heuristic and Nearest Neighbor, focusing on minimizing distance and fuel consumption. The data used includes depot locations, agent points, demand volumes, vehicle types, and geographic coordinates. Simulation results show that the implementation of both methods yields significant savings compared to actual routes. The Nearest Neighbor method achieves distance savings of 61,14% (motorcycles) and 61,52$ (cars), and fuel consumption savings of 51,30% (motorcycles) and 52,15% (cars). Meanwhile, the Clarke-Wright Savings Heuristic method resulted in distance savings of 58,66% (motorcycles) and 57,08% (cars), and fuel consumption savings of 48,18% (motorcycles) and 46,63% (cars). With this approach, the company can reduce distribution costs and improve overall logistic efficiency.